The potency of alpha lipoic acid as anti inflammatory on the complete freund's adjuvant-induced rheumatoid arthritis in rat model - Megawati, Selvi; Rahmadi, Mahardian; Susilo, Imam; Khotib, Junaidi (Folia Medica Indonesiana, 2017)
Rheumatoid arthritis (RA) is an autoimmune diseases which is characterized by chronic inflammation of the synovial tissue in joints. This research was designed to investigate the effect of alpha lipoic acid as antioxidant on rats with complete freund's adjuvant (CFA)-induced RA by intra articular injection of complete freund's adjuvant (CFA). ALA was administered orally once a day for 7 days at 30, 60 and 120 mg doses a week after CFA injection. The severity of arthritis was evaluated by joint diameter and latency time on thermal stimulation. Joint diameter and latency time on thermal stimulation will measured on day 0, 3, 5, 7, 10, 12 and 14. Measurement of malondialdehyde (MDA) level in plasma was performed using thiobarbituric acid (TBA) method to assess lipid peroxidation. Histology of joint was examined by microscope following hematoxylin-eosin staining. The result showed that treatment with ALA at 30 mg and 60 mg significantly decreased the joint diameter compared to CFA group (p=0.003; p=0.001 respectively) and rat's latency time on thermal stimulation was also significantly increased compared to CFA group (p=0.015; p=0.026 respectively). Measurement of MDA in CFA group and ALA group had no significant difference. Histological staining indicated that the recovery of the synovial membranes of joint in ALA group had no effect. Results indicated that ALA has the effect to suppress the development of inflammation in RA but not through oxidative stress pathway.